Third metal stent for revision of malignant hilar biliary strictures - Lee, Tae Hoon; Moon, Jong Ho; Choi, Hyun Jong; Lee, Yun Nah; Choi, Moon Han; Cha, Sang Woo; Cho, Young Deok; Park, Sang-Heum; Kim, Sun-Joo (Endoscopy, 2016)
Background and study aim: Endoscopic stent-in-stent (SIS) placement of multiple metal stents is technically demanding. In the present study, we explored the technical feasibility and efficacy of endoscopic deployment of a third metal stent to create a triple SIS placement in patients with a bilateral SIS configuration for inoperable high grade malignant hilar biliary stricture (HBS) that had failed clinically.Methods: Eighteen patients with histologically proven inoperable HBS underwent deployment of an additional third metal stent as a revisionary method after early clinical failure following technically successful bilateral SIS placement using cross-wired metal stents. The main outcome measures were the technical and clinical success rates, and adverse events.Results: The overall technical and clinical success rates were 88.9 % (16/18) and 87.5 % (14/16), respectively. The early and late complications were cholangitis (n = 2) and cholecystitis (n = 1). Stent occlusion developed in 35.7 % (5/14) of patients in whom a third metal stent for revision of a bilateral SIS configuration was clinically successful. The median (range) times for stent patency and patient survival were 176 days (49 – 372) and 216 days (52 – 384), respectively.Conclusions: Endoscopic deployment of an additional third metal stent into a bilateral SIS configuration was technically feasible and effective in patients with inoperable high grade malignant HBS in whom bilateral SIS placement had failed clinically.